Influences of Dietary Vitamin E, Selenium-Enriched Yeast, and Soy Isoflavone Supplementation on Growth Performance, Antioxidant Capacity, Carcass Traits, Meat Quality and Gut Microbiota in Finishing Pigs - Cui Zhu; Jingsen Yang; Xiaoyan Nie; Qiwen Wu; Li Wang; Zongyong Jiang (MDPI AG, 2022)
This study investigated the effects of dietary compound antioxidants on growth performance, antioxidant capacity, carcass traits, meat quality, and gut microbiota in finishing pigs. A total of 36 barrows were randomly assigned to 2 treatments with 6 replicates. The pigs were fed with a basal diet (control) or the basal diet supplemented with 200 mg/kg vitamin E, 0.3 mg/kg selenium-enriched yeast, and 20 mg/kg soy isoflavone. Dietary compound antioxidants decreased the average daily feed intake (ADFI) and feed to gain ratio (F/G) at d 14-28 in finishing pigs (p < 0.05). The plasma total protein, urea nitrogen, triglyceride, and malondialdehyde (MDA) concentrations were decreased while the plasma glutathione (GSH) to glutathione oxidized (GSSG) ratio (GSH/GSSG) was increased by compound antioxidants (p < 0.05). Dietary compound antioxidants increased loin area and b* value at 45 min, decreased backfat thickness at last rib, and drip loss at 48 h (p < 0.05). The relative abundance of colonic Peptococcus at the genus level was increased and ileal Turicibacter_sp_H121 abundance at the species level was decreased by dietary compound antioxidants. Spearman analysis showed a significant negative correlation between the relative abundance of colonic Peptococcus and plasma MDA concentration and meat drip loss at 48 h. Collectively, dietary supplementation with compound antioxidants of vitamin E, selenium-enrich yeast, and soy isoflavone could improve feed efficiency and antioxidant capacity, and modify the backfat thickness and meat quality through modulation of the gut microbiota community.